Acetate Regulation of Spore Formation Is under the Control of the Ras/Cyclic AMP/Protein Kinase A Pathway and Carbon Dioxide in Saccharomyces cerevisiae - Jungbluth, Marc (American Society for Microbiology, 2012)
In Saccharomyces cerevisiae, the Ras/cyclic AMP (cAMP)/protein kinase A (PKA) pathway is a nutrient-sensitive signaling cascade that regulates vegetative growth, carbohydrate metabolism, and entry into meiosis. How this pathway controls later steps of meiotic development is largely unknown. Here, we have analyzed the role of the Ras/cAMP/PKA pathway in spore formation by the meiosis-specific manipulation of Ras and PKA or by the disturbance of cAMP production. We found that the regulation of spore formation by acetate takes place after commitment to meiosis and depends on PKA and appropriate A kinase activation by Ras/Cyr1 adenylyl cyclase but not by activation through the Gpa2/Gpr1 branch. We further discovered that spore formation is regulated by carbon dioxide/bicarbonate, and an analysis of mutants defective in acetate transport (ady2Δ) or carbonic anhydrase (nce103Δ) provided evidence that these metabolites are involved in connecting the nutritional state of the meiotic cell to spore number control. Finally, we observed that the potential PKA target Ady1 is required for the proper localization of the meiotic plaque proteins Mpc70 and Spo74 at spindle pole bodies and for the ability of these proteins to initiate spore formation. Overall, our investigation suggests that the Ras/cAMP/PKA pathway plays a crucial role in the regulation of spore formation by acetate and indicates that the control of meiotic development by this signaling cascade takes places at several steps and is more complex than previously anticipated.